Blood-based traumatic brain injury biomarkers – Clinical utilities and regulatory pathways in the United States, Europe and Canada. (2nd December 2021) - Wang, Kevin K.; Munoz Pareja, Jennifer C.; Mondello, Stefania; Diaz-Arrastia, Ramon; Wellington, Cheryl; Kenney, Kimbra; Puccio, Ava M.; Hutchison, Jamie; McKinnon, Nicole; Okonkwo, David O.; Yang, Zhihui; Kobeissy, Firas; et al.
ABSTRACT: Introduction: Traumatic brain injury (TBI) is a major global health issue, resulting in debilitating consequences to families, communities, and health-care systems. Prior research has found that biomarkers aid in the pathophysiological characterization and diagnosis of TBI. Significantly, the FDA has recently cleared both a bench-top assay and a rapid point-of-care assays of tandem biomarker (UCH-L1/GFAP)-based blood test to aid in the diagnosis mTBI patients. With the global necessity of TBI biomarkers research, several major consortium multicenter observational studies with biosample collection and biomarker analysis have been created in the USA, Europe, and Canada. As each geographical region regulates its data and findings, the International Initiative for Traumatic Brain Injury Research (InTBIR) was formed to facilitate data integration and dissemination across these consortia. Areas Covered: This paper covers heavily investigated TBI biomarkers and emerging non-protein markers. Finally, we analyze the regulatory pathways for converting promising TBI biomarkers into approved in-vitro diagnostic tests in the United States, European Union, and Canada. Expert Opinion: TBI biomarker research has significantly advanced in the last decade. The recent approval of an iSTAT point of care test to detect mild TBI has paved the way for future biomarker clearance and appropriate clinical use across the globe.